2007
DOI: 10.1139/g07-007
|View full text |Cite
|
Sign up to set email alerts
|

Development, characterization, and comparative analysis of polymorphism at common bean SSR loci isolated from genic and genomic sources

Abstract: Microsatellites or SSRs (single sequence repeats) have been used to construct and integrate genetic maps in crop species, including Phaseolus vulgaris. In the present study, 3 cDNA libraries generated by the Bean EST project (http://lgm.esalq.usp.br/BEST/), comprising a unigene collection of 3126 sequences and a genomic microsatellite-enriched library, were analyzed for the presence of SSRs. A total of 219 expressed sequence tags (ESTs) were found to carry 240 SSRs (named EST-SSR), whereas 714 genomic sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
85
3
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 42 publications
14
85
3
10
Order By: Relevance
“…Cabral et al locus varied from 2 to 4, with a mean of 2.23; primer SSR BM141 gave the largest number of alleles. Similar numbers of alleles per locus were found for beans by Campos et al (2007), Hanai et al (2007) and Cardoso (2009).…”
Section: Resultssupporting
confidence: 85%
“…Cabral et al locus varied from 2 to 4, with a mean of 2.23; primer SSR BM141 gave the largest number of alleles. Similar numbers of alleles per locus were found for beans by Campos et al (2007), Hanai et al (2007) and Cardoso (2009).…”
Section: Resultssupporting
confidence: 85%
“…The core map is composed of some 550 markers, including RFLP, RAPD, SCAR, allozyme, and seed protein markers; when considering markers from the other, correlated maps, at least 1000 markers have been mapped which would average one marker per 1-2 cM (Freyre et al, 1998;Gepts, 1999;Kelly et al, 2003, Miklas et al, 2006. Another development in the genetic mapping of the bean genome includes the development of simple sequence repeat (SSR) or microsatellite markers (Yu et al, 1999(Yu et al, , 2000bBlair et al, 2003;Melotto et al, 2005;Hanai et al, 2007). The first preliminary study of the existence of microsatellite markers in the bean genome was conducted by Yu et al (1999Yu et al ( , 2000b, who were able to map 15 of the SSR markers onto the core linkage map.…”
Section: Genomic Mapping Of Bean With Mmsmentioning
confidence: 99%
“…Therefore these studies bring to a total of 115 microsatellite loci on the common bean genetic map, and provides coverage for every chromosome in the genome with from five to 20 SSR markers each (Blair et al, 2003). Two hundreds forty-three SSR sequences were identified from 5,255 bean expressed sequence tag (EST) sequences (Melotto et al, 2005) and 471 SSRs were found from 714 genomic sequences in a microsatellite-enriched genomic library (Hanai et al, 2007). These SSR markers will be invaluable for fine mapping the bean genome and tagging genes of economic interest.…”
Section: Genomic Mapping Of Bean With Mmsmentioning
confidence: 99%
“…Given the high polymorphism level of microsatellites when compared to other markers, many worldwide researchers have preferred using these markers on the study of common bean population structure, genetic divergence and genetic mapping (Díaz and Blair 2006, Hanai et al 2007, Campos et al 2011.…”
Section: Using Microsatellite In Genetic Diversity and Population Strmentioning
confidence: 99%